The Impact of Lipid Handling and Phase Distribution on the Acoustic Behavior of Microbubbles - Simone A.G. Langeveld; Inés Beekers; Gonzalo Collado-Lara; Antonius F. W. van der Steen; Nico de Jong; Klazina Kooiman (MDPI AG, 2021)
Phospholipid-coated microbubbles are ultrasound contrast agents that can be employed for ultrasound molecular imaging and drug delivery. For safe and effective implementation, microbubbles must respond uniformly and predictably to ultrasound. Therefore, we investigated how lipid handling and phase distribution affected the variability in the acoustic behavior of microbubbles. Cholesterol was used to modify the lateral molecular packing of 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC)-based microbubbles. To assess the effect of lipid handling, microbubbles were produced by a direct method, i.e., lipids directly dispersed in an aqueous medium or indirect method, i.e., lipids first dissolved in an organic solvent. The lipid phase and ligand distribution in the microbubble coating were investigated using confocal microscopy, and the acoustic response was recorded with the Brandaris 128 ultra-high-speed camera. In microbubbles with 12 mol% cholesterol, the lipids were miscible and all in the same phase, which resulted in more buckle formation, lower shell elasticity and higher shell viscosity. Indirect DSPC microbubbles had a more uniform response to ultrasound than direct DSPC and indirect DSPC-cholesterol microbubbles. The difference in lipid handling between direct and indirect DSPC microbubbles significantly affected the acoustic behavior. Indirect DSPC microbubbles are the most promising candidate for ultrasound molecular imaging and drug delivery applications.